Towards a discourse and governmentality approach to spatial development – the case of inner city shopping centres - Guth, Denis; Pütz, Robert (Raumforschung und Raumordnung | Spatial Research and Planning, 2020)
Using the example of the political-planning discourse on former plans to develop a large-scale shopping centre in the inner city of Mainz, the potential benefits of a discourse and governmentality approach to spatial research subjects is discussed. In particular, the discursive discursive mechanisms of inscribing an entrepreneurial and depoliticized conception of urban space into apparently neutral and objective techniques of spatial analysis are worked out. At the same time, this idea of urban space as a competitive entity determined by spatio-economic principles is challenged by competing conceptions of urban development focused on the conservation of place-specific structures of the built environment. Thus, the case study illustrates how discourse analysis can excavate the spatial knowledge structures guiding the management of contemporary urban development projects.